The speech of the prophets with their people in the Holy Quran (Journal of the College of Basic Education, 2023)
The idea of the research came to focus on the highness of the speech of the prophets to their people, although it is opposed by them to respond and harm the prophets and their followers. Despite this wandering and misguidance emanating from their people, and with the intransigence and practice of various methods of oppression and brutality against their prophets, they were commanded with soft words, wisdom, and good exhortation, so the methods of their calls were united in content, different in legislation, to reach the goal of moderation in the speech of the prophets to their people. God Almighty did not tell us these stories in vain, but in order to take a lesson from them, from here it is necessary to achieve complete imitation and imitation of the morals of the prophets, peace be upon them, in adopting moderate discourse even with those who differ in the approach, because what cannot be achieved by force can be achieved by softness and rhetoric. Moderate, and let the prophetic approach in discourse be the path that we follow in all our dealings, whether with those who agree or disagree with us in thought and approach.